Fuzzy adaptive controller based on the Lyapunov Theory for control of the dual star induction machine, ISSN 1582-4594 - Tahar Laamayad; Naceri Farid; Abdessemed Rachid (Journal of Electrical Engineering, Roumanie, 2013)
In this paper a design of the fuzzy adaptive control(FAC) based on the lyapunov stability theory for improving the dynamic response of the double star induction machine (DSIM) is presented, the fuzzy adaptive control scheme gives fast dynamic response with no overshoot, it has an important feature of being highly robust, insensitive to plant parameters variations, the design procedure is established to control the speed of the machine,the simulation results show that the controller in enhancing the robustness of control systems with high accuracy.